Analisis Nilai Tambah Biji Kopi Sangrai Pada Revaco Coffee Roastery Di Kelurahan Komo Kecamatan Wenang Kota Manado - Mamonto, Ersa; Waney, Nordy Fritsgerald Lucky; Baroleh, Jenny (Sam Ratulangi University, 2024)
This study aims to analyze the amount of added value from raw coffee beans to roasted coffee beans at Revaco Coffee Roastery business in Komo Village, Wenang District, Manado City. The research was conducted for two months from July to August 2023. The research was conducted at the roasted coffee bean business at Revaco Coffee Roastery in Komo Village, Wenang District, Manado City, North Sulawesi. The data collection method in this research is the case study method. The data used is roasted coffee bean production data which becomes raw coffee beans at the Revaco Coffee Roastery business produced August 13, 2023, which is obtained from the results of direct interviews with business owners and employees at the roasted coffee bean business at Revaco Coffee Roastery. Data analysis used in this study using product value added analysis. The results showed that the Revaco Coffee Roastery roasted coffee bean business found that the added value of processing 54 kilograms of raw coffee beans into roasted coffee beans was IDR 76,613.54 per kilogram.